Idades U-Pb de zircão detríticos e suas implicações na proveniência de sedimentos da porção inferior da formação Penedo, bacia de Sergipe-Alagoas, NE Brasil - Melo, Alice Maria Queiroz de (2017)
Among the several techniques used for provenance studies, the geochronological analysis associated to paleocurrent survey has presented excellent results. Therefore, this study aimed to identifying the sources of the sandstone at the outcrop that gave name to the Penedo Formation, inserted in the Sergipe-Alagoas Basin. This outcrop is located at Penedo’s city, state of Alagoas, northeast of Brazil. The methodology consisted of a continuous bibliographical survey; field work for sample collection and paleocurrent analysis; preparation of samples for concentration of the detrital zircon crystals; chemical-isotopic determination of the crystals with the U-Pb dating, by Laser Ablation Mass Spectrometer (LA-ICP-MS); data processing and the elaboration of this dissertation. The sedimentary record of paleocurrents indicated a contribution coming from north, while the analyzed crystals indicated ages ranging from Mesoarchean (3,098 ± 33 Ma) to Paleozoic (530 ± 12 Ma). This set of ages is related to five groups of sources: Neoproterozoic granites related to the Brasiliano cycle; Mesoproterozoic rocks of the Cabrobró Complex; rocks of the Paleoproterozoic basement coming from the Arapiraca Complex; and finally, rocks of Neo and Mesoarquean ages from rocks of the “Domo Jirau do Ponciano”, south of Alagoas state. Further work with the chemical characterization of zircon crystals of various igneous lithotypes (presented in this dissertation in the form of annex), indicated that these crystals of the Penedo Formation were largely provided from basic igneous or mantle affinity rocks, which ratifies the sources identified here by geocrology and paleocurrent analysis.